2020
DOI: 10.1002/pen.25625
|View full text |Cite
|
Sign up to set email alerts
|

A modus operandi toward interfacial enhancement of ethylene propylene diene monomer rubber/ polybenzoxazine blends using EPDM‐graftedvinyltrimethoxysilane copolymer

Abstract: Compatibilization of polymer blends is performed to obtain synergistic effects in physical and mechanical properties. The present work demonstrates the ability of vinyltrimethoxysilane‐grafted‐ethylene propylene diene monomer rubber (VTMS‐g‐EPDM) to improve the compatibility between EPDM and polybenzoxazine (PB). EPDM reacted with 5 phr of VTMS showed the highest grafting efficiency as well as a relatively low gel content, and was added to EPDM/PB blends. The addition of 8 phr of compatibilizer to 70/30 (w/w) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[ 27,59 ] It also confirmed that the introduction of iron(III) ions on the basis of PMAFe0–30% formed a dynamic crosslinking network of hydrogen bonding and coordination bonding. [ 60,61 ] Moreover, the modified elastomer still had low T g (<−35°C), which showed that it has good elasticity at low temperature. These thermodynamic analyses showed that the thermal stability of PMAFe/POE elastomers was improved by introducing hydrogen bonding and iron‐based coordination bonding dynamic crosslinking network.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27,59 ] It also confirmed that the introduction of iron(III) ions on the basis of PMAFe0–30% formed a dynamic crosslinking network of hydrogen bonding and coordination bonding. [ 60,61 ] Moreover, the modified elastomer still had low T g (<−35°C), which showed that it has good elasticity at low temperature. These thermodynamic analyses showed that the thermal stability of PMAFe/POE elastomers was improved by introducing hydrogen bonding and iron‐based coordination bonding dynamic crosslinking network.…”
Section: Resultsmentioning
confidence: 99%
“…This is also the reason for the high value of grafting efficiency. [24] The molecular weight of grafted polymer chains depends on the conditions of copolymer synthesis and is determined by the kinetics and parameters of grafting. [7] The molecular weight of the grafted PAA chains was determined from the degree of conversion, the concentration of AA and PP, and the efficiency of grafting (Table 1).…”
Section: Grafting Parametersmentioning
confidence: 99%
“…[23] On the other hand, graft copolymerization has a positive effect on the interfacial surface and improves compatibility in polymer systems. [24,25] In most cases, the values of the kinetic parameters of graft copolymerization differ from those of the radical polymerization of monomers. In the case of graft copolymerization of sodium styrenesulfonate on polyvinylidene fluoride films irradiated with an electron beam, the order of the reaction with respect to the concentration of the monomer and initiator turned out to be 2.84 and 1.20, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–6 ] Ethylene Propylene Diene Monomer (EPDM), a terpolymer of ethylene, propylene, and non‐conjugated diene with excellent properties, such as low density, oil resistance, ablation resistance, and heat and oxygen aging, can be used in the preparation of sealing rings, hoses, thermal insulation layers, and military products. [ 7–12 ]…”
Section: Introductionmentioning
confidence: 99%